Bacteria-Mediated Synthesis of Silver and Silver Chloride Nanoparticles and Their Antimicrobial Activity - Ghiuta, Ioana; Croitoru, Catalin; Kost, Joseph; Wenkert, Rodica; Munteanu, Daniel (MDPI- Applied Sciences, 2021)
Within the frame of this work, the synthesis of silver nanoparticles (Ag NPs) and silver chloride nanoparticles (AgCl NPs) as mediated by microbes has been investigated. The nanoparticles were reduced from a silver nitrate precursor by the presence of bacteria, like Raoultella planticola and Pantoea agglomerans. The results show that the characteristic surface plasmon resonance absorption band occurs at about 440 nm. Nanoparticles were also characterized with the help of scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM), and X-ray diffraction (XRD), which showed the formation of spherical Ag/AgCl NPs with a centered cubic crystal structure and a mean particle size of around 10–50 nm. Assays for antimicrobial activity of the biosynthesized nanoparticles demonstrated meaningful results against microorganisms such as Staphylococcus aureus, Streptococcus pyogenes, Salmonella, and Bacillus amyloliquefaciens. Furthermore, this study shows that the combination of the obtained nanoparticles with standard antibiotics may be useful in the fight against emerging microbial drug resistance.
Keywords: silver chloride; nanoparticles; Pantoea agglomerans; Raoultella planticola; antibacterial properties